(untitled) (Res Medica, 2014)
The key to becoming a good doctor is acquiring a solid foundation in the skills of listening to and examining patients. The importance of a thorough grounding in these skills had been recognized and prompted the current revision of the phase II course, the objective being to improve the introduction to clinical studies.